Assessing the awareness of emerging digital technologies among students in architectural education in Ghana - Elom Ayeke; Emmanuel Appiah Acheampong; Ishmael Bekoe; Jeannette Attipoe (Discover Education)
Abstract The twenty-first century has become synonymous with two primary architectural concepts: sustainability and digital technologies. While the former seeks less carbon footprint within the built environment, the latter drives a novel approach towards efficient and effective productivity. However, previous findings show inadequate study on Emerging Digital Technologies (EDTs) and their Awareness in Higher Educational Institutions (HEIs), especially in the Global South. In light of this, the study primarily aims to evaluate the perceived Awareness of students of EDTs within architectural educational institutions in Ghana. The study used a quantitative approach, obtaining data from 243 respondents using a questionnaire. Findings revealed students were aware of most EDTs, indicating an interest specifically in Computer-Aided Design and Building Information Modelling software. However, the students perceived little Awareness and interest in robotics and nanotechnology. Furthermore, the students perceived that inadequate tools and equipment are vital influences that limit their Awareness of EDTs. The authors recommend that HEIs review curricula to incorporate EDTs and collaborate with digital agencies to create an effective environment for students to increase their interest and proficiency in EDTs in architecture. There should also be continuous capacity building for the architectural HEI staff to ensure the transfer of relevant skills in contemporary EDTs in the industry. Moreover, further studies must be conducted into a standardized framework for introducing EDTs in architectural education.